Prevalence of psychological symptoms in low and high-risk pregnant women: A cross-sectional study - Maryam Dalili; Ali Mehdizadeh; Maryam Nodinnejad; Fatemeh Karami Robati (International Journal of Reproductive BioMedicine)
Background: Common psychological disorders during pregnancy can have obvious harmful effects on both mother and fetus.